Spectrum of Imaging Findings in Oriental Cerebral Schistosomiasis and Their Categorization by MRI (Nepalese Journal of Radiology, 2020)
Introduction: To describe the spectrum of imaging findings in oriental cerebral schistosomiasis and characterizing different stages by MRI.Methods: A retrospective review of the clinical and MRI images of twenty nine pathologically proven cases of neuroschistomiasis was performed. Patients with either absence of complete MR examination, previously treated patients were excluded from the study. MRI images were analyzed and lesions were evaluated for the following parameters - distribution, size, clusterity, perilesional edema, mass effect, intralesional hemorrhage, necrosis, cystic degeneration, any abnormal enhancements, any atypical features as abscess,vasculitis, infarctions, or focal atrophy and encephalomalacia.Results: Lesions were only supratentorial in 25 cases, only infratentorial in 3 cases while were both supratentorial and infratentorial in 1 case. Lesions were unilateral in 26 cases. Significant mass effect was noted in 8 cases. All nodular and mass lesions were hyperintense or isointense in T1WI while all but two lesions were hyperintense in T2WI. Lesions were predominantly as clustered nodules (12 cases). All nodules enhanced homogeneously except three that demonstrated ring like enhancement. Masses were demonstrated either homogeneous (2 cases) or heterogeneous in enhancement (2 cases). Central linear enhancement was noted in 12 cases, leptomeningeal enhancement in 10 cases while gyral enhancement was noted in 1 case.Conclusions: Radiological presentation of neuroschistosomiasis varies at different stages of infection as well as among the asymptomatic groups. Recognition of spectrum of presentation has an implied role in the overall management and outcome in cases